Managing Knowledge in Organizations : Summary of an Interview with Marshall Van Alstyne and Hind Benbya - Leonard, Aaron (2012)
Knowledge exchange among practitioners in low- and middle-income countries is now at the forefront of global development policy formulation. But the question of how to connect the right people with the right knowledge at the right time isnt new. Knowledge Management (KM) has been an established discipline since the 1990s. We talked with MITs Marshall Van Alstyne and Montpelliers Hind Benbya about the state of knowledge management and information exchange in organizations today, and how new practices like knowledge markets can help us find better solutions to some of todays trickiest development challenges.